2016
DOI: 10.17736/ijope.2016.fvr01
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Measured and Simulated Structural Loads of an Offshore Wind Turbine at Alpha Ventus

Abstract: A comparison of fatigue and extreme loads from simulations with full-scale measurements collected over a period of ten months in the offshore test field, Alpha Ventus, is presented in this paper. There are two goals of this study: (1) to check if the measured range of fatigue and extreme loads can be captured correctly by simulations when the variations of relevant environmental parameters are taken into account; and (2) to investigate if measured extreme loads can be reproduced by simulations when ten-minute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…For a more accurate, fully probabilistic design an approach is required which considers the load uncertainties imposed by the varying environmental conditions. In Müller and Cheng (2016) we indicated that a simple lumping of load cases as performed in standard procedures may miss important load variation which is observed on the real turbine. In a follow-up presented in Müller et al (2016) we showed that the spreading of full-scale environmental fatigue loads can be reproduced by state-of-the-art simulation tools when using appropriate methods for the selection of the environmental combinations.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…For a more accurate, fully probabilistic design an approach is required which considers the load uncertainties imposed by the varying environmental conditions. In Müller and Cheng (2016) we indicated that a simple lumping of load cases as performed in standard procedures may miss important load variation which is observed on the real turbine. In a follow-up presented in Müller et al (2016) we showed that the spreading of full-scale environmental fatigue loads can be reproduced by state-of-the-art simulation tools when using appropriate methods for the selection of the environmental combinations.…”
Section: Introductionmentioning
confidence: 94%
“…Hence, if looking at damage contribution the results of this study have to be adjusted accordingly and lead to a slower convergence. In Müller and Cheng (2016), we obtained a damage uncertainty (range of 95 percentiles for different wind speeds) for fixed bottom offshore fatigue simulations according to International Electrotechnical Commission (2009) between 10 and 20 %. To reach the same uncertainty in this study, 200-500 samples are required (see Fig.…”
Section: Damage Contribution From High Del Events (Impact Of Outliers)mentioning
confidence: 99%
See 1 more Smart Citation
“…That is why there exist several approaches to decrease the computing time by using meta models for fatigue damages. Examples are Zwick and Muskulus, Müller et al, Toft et al, or Stewart . Zwick and Muskulus reduced the number of simulations by a factor of 7 without adding a significant amount of additional uncertainty by applying a multivariate linear regression.…”
Section: Introductionmentioning
confidence: 99%
“…Three existing drawbacks according to the state of the art are treated in this study. Firstly, environmental conditions are no longer treated as constant within each wind speed bin, as Müller et al found out that variable environmental conditions can reproduce measurement variability more precisely. Secondly, so far, mainly jacket and floating substructures were investigated.…”
Section: Introductionmentioning
confidence: 99%